Buka's Emergencies in Dermatology - Buka, Bobby; Uliasz, Annemarie; Krishnamurthy, Karthik (Springer New York : Imprint: Springer, 2013)
The term "dermatologic emergency" is rarely used, and a dermatologist is typically not the first physician called when a patient presents to the emergency department. However, largely under-recognized dermatoses can be life-threatening if not diagnosed and treated in a timely fashion. Buka's Emergencies in Dermatology addresses the need for a concise, portable reference that can be used by emergency personnel, dermatologists and resident-physicians. This text, heavily illustrated with color images, proves to be especially critical if a community-based hospital does not have a dermatology department and the responsibility for initial diagnosis falls to the emergency room or critical care physician. While the vast majority of cutaneous outbreaks are not life-threatening, those that are can go unrecognized with devastating consequences. Buka's Emergencies in Dermatology addresses this concern and focuses on the most critical issues in cutaneous emergencies, from neonatal and pediatric emergencies, to infectious emergencies and drug eruptions.